Pilot studies of pressure-immobilization bandages for rattlesnake envenomations - Meggs, William Joel; Courtney, Christine; O'Rourke, Dorcas; Brewer, Kori Louise (Clinical toxicology (Philadelphia, Pa.), 2010)
Study objective. Pressure-immobilization bandages sequester venom in extremities and are recommended for snakebites without local toxicity. Pilot studies were performed to determine the time of onset of toxicity and efficacy of pressure-immobilizations bandages in a porcine model of rattlesnake envenomation. Methods. After IACUC approval, anesthetized pigs were injected subcutaneously in a distal hind leg with 200 mg of Crotalus atrox venom. After 1 min, pigs received either a pressure-immobilization bandage (N = 3) or no treatment (N = 3). At 24 h, surviving pigs received antivenin and then the pressure-immobilization bandages were removed. Surviving subjects were followed for 1 week. Chi-square analysis and paired t-test were used. Results. Pigs with pressure-immobilization bandages survived for 24 h, whereas untreated pigs died at 13.68 ± 3.42 h (p = 0.014). Surviving pigs walked on the extremity at 7 days. Potassium rose from 4.033 ± 0.252 at baseline to 17.767 ± 5.218 mEq L (p < 0.0001) at time of death in untreated pigs but was normal at 24 h in treated subjects. Widespread tissue necrosis was seen in the untreated group but only local necrosis in the treatment group. Conclusions. Pressure-immobilization bandages prevented death from severe C. atrox envenomations with a 24 h delay to treatment. Surviving pigs had recovery of limb use at 1 week.